Effect of change in cell substrate on the critical quality attributes of L-Zagreb Mumps vaccine manufactured using parallel plate bioreactor. (September 2020) - Muley, Ravindra; Dhere, Rajeev
Abstract: Leningrad-Zagreb strain of mumps vaccine virus was grown on two different cell substrates viz. MRC-5 cells and Vero cells besides its original cell substrate i.e. Chicken Embryo Cells. Homogeneous virus pools prepared from each set of experiments were then lyophilized as per standard in-house protocol. Critical Quality Attributes (CQAs) such as the titer of the bulk vaccine and potency and stability of the lyophilized vaccine were then estimated using the CCID50 method to understand the lyophilization losses and thermal losses respectively in the vaccine. Another CQA viz. the genetic homogeneity of the vaccine was also tested using the single base extension method for identifying the nucleotides present at the three known locations of single nucleotide polymorphism (SNP). Comparison of CQA results across different cell substrates indicated encouraging results for Vero cell grown L-Zagreb virus compared to the MRC-5 cells grown L-Zagreb mumps virus. Significant improvement in productivity was also observed in the dynamic culture conditions compared to the static culture conditions. Progressive work in this research area can lead to development of a cGMP manufacturing process for mumps vaccine with easy scale up potential in future.